2019
DOI: 10.1021/acsphotonics.9b00245
|View full text |Cite
|
Sign up to set email alerts
|

Delocalized Hot Electron Generation with Propagative Surface Plasmon Polaritons

Abstract: Hot electrons generated within plasmonic structures possess a high kinetic energy that can be employed to drive and catalyze a huge range of physicochemical processes at the metallic interface. Up to now, these photogenerated hot carriers were mainly generated within simple plasmonic nanoparticles where hot carrier localization coincides spatially with the position optical excitation. A current challenge for the development of future plasmonic-based hot electron devices requires the ability for a delocalized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…According to the reconstructed plasmon-enhanced electric field E(t) from these measurements, the pulse duration and thus the dephasing time can be derived. On the other aspect, the hot-carrier relaxation dynamics on the time scales of picoseconds have been studied by multiphoton photoluminescence (MPPL) [28][29][30] . The temporal response of the carriers' relaxation extending from sub-to several picoseconds has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…According to the reconstructed plasmon-enhanced electric field E(t) from these measurements, the pulse duration and thus the dephasing time can be derived. On the other aspect, the hot-carrier relaxation dynamics on the time scales of picoseconds have been studied by multiphoton photoluminescence (MPPL) [28][29][30] . The temporal response of the carriers' relaxation extending from sub-to several picoseconds has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic metal nanostructures allow us to strongly enhance light absorption and emission in extremely thin transition metal dichalcogenide (TMD) layers. Thus, intensive research effort has focused on exploring the novel physical phenomena in TMD/metal hybrid nanostructures. Both localized surface plasmon (LSP) and surface plasmon polariton (SPP) effects can strongly confine light near metal nanostructures, but they have some distinct physical features.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LSP resonance appears when an incoming photon has a suitable energy. , In contrast, SPP excitation occurs when an incoming photon has appropriate energy, polarization, and incident angle . With the help of the propagating SPP, TMD/metal nanostructures can exhibit selective excitation of SPP modes, amplification of a specific exciton, strong exciton–plasmon coupling, ultrafast hot electron transfer, or delocalized hot carrier production. These intriguing physical phenomena have potential for various applications, such as photodetectors, light-emitting devices, polariton lasers, optoelectronic circuit elements, and photocatalysts. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, high‐quality graphene encapsulated between two h‐BN films possesses plasmons that exhibit unprecedentedly low damping combined with strong field confinement, HPs in h‐BN can be controlled by crystal thickness, HPs in MoO 3 crystals display in‐plane anisotropy with high confinement and low loss, and the propagating direction of HPs can be controlled by metasurfaces . Numerous studies have demonstrated applications of s‐SNOM nanoimaged vdW polaritons, including hot electron detection, surface‐enhanced infrared (IR) absorption, ultrafast plasmonic switching, observation of slow light, metasurface engineering, hyperfocusing lens, and probing optical constants …”
Section: Introductionmentioning
confidence: 99%